Continuous hemodynamics monitoring during arteriovenous malformation microsurgical resection with laser speckle contrast imaging: case report - Dimanche, Alexis; Miller, David R.; Goldberg, Johannes; Raabe, Andreas; Dunn, Andrew K.; Bervini, David (Frontiers in Surgery, 2023)
AVM surgery is challenging due to progressive and often unforeseeable flow changes during its resection which involve both the AVM and the surrounding brain tissue. Hence, accurate monitoring of blood flow is crucial to minimize complications and improve outcomes. The following case report illustrates the usefulness of complimentary non-invasive tools that can provide real time blood flow assessment. We present a case demonstrating the application of laser speckle contrast imaging (LSCI) in evaluating vessel flow dynamics during AVM surgery. A 30-year-old female presented with sudden headaches, nausea, vomiting, and vertigo. Emergency imaging revealed a ruptured cerebellar AVM necessitating surgical intervention. LSCI was integrated into the surgical workflow, providing continuous visualization of relative cerebral blood flow (rCBF) of vessels surrounding the AVM. Before AVM resection, LSCI measurements revealed the arterialized vasculature supplying the AVM nidus; measurements after AVM resection showed significant hemodynamic changes including normal flow in the initially arterialized AVM draining veins and adjacent arterial branches. LSCI also detected blood flow alterations during temporary occlusion, enabling assessment of downstream vascular regions. In conclusion, we provide an example supporting the utility of LSCI for real-time hemodynamic monitoring during AVM resection surgery. LSCI offers non-invasive, continuous, and immediate blood flow information, complementing conventional imaging methods like indocyanine green angiography. Additionally, our findings suggest that LSCI has the potential to provide a non-invasive means of identifying the specific superficial vessel branches or cortical areas that receive blood supply from a particular vessel.